Variational Iteration Method for Solving the Generalized Degasperis-Procesi Equation - Qian Lijuan; Tian Lixin; Ma Kaiping (Abstract and Applied Analysis)
We introduce the variational iteration method for solving the generalized Degasperis-Procesi equation. Firstly, according to the variational iteration, the Lagrange multiplier is found after making the correction functional. Furthermore, several approximations of un+1(x,t) which is converged to u(x,t) are obtained, and the exact solutions of Degasperis-Procesi equation will be obtained by using the traditional variational iteration method with a suitable initial approximation u0(x,t). Finally, after giving the perturbation item, the approximate solution for original equation will be expressed specifically.